Antibacterial honey for the prevention of peritoneal-dialysis-related infections (HONEYPOT): a randomised trial - Johnson, David W; Badve, Sunil V; Pascoe, Elaine M; Beller, Elaine; Cass, Alan; Clark, Carolyn; de Zoysa, Janak; Isbel, Nicole M; McTaggart, Steven; Morrish, Alicia T; Playford, E Geoffrey; Scaria, Anish; et al. (The Lancet infectious diseases, 2014)
There is a paucity of evidence to guide the best strategy for prevention of peritoneal-dialysis-related infections. Antibacterial honey has shown promise as a novel, cheap, effective, topical prophylactic agent without inducing microbial resistance. We therefore assessed whether daily application of honey at the exit site would increase the time to peritoneal-dialysis-related infections compared with standard exit-site care plus intranasal mupirocin prophylaxis for nasal carriers of Staphylococcus aureus. In this open-label trial undertaken in 26 centres in Australia and New Zealand, participants undergoing peritoneal dialysis were randomly assigned in a 1:1 ratio with an adaptive allocation algorithm to daily topical exit-site application of antibacterial honey plus standard exit-site care or intranasal mupirocin prophylaxis (only in carriers of nasal S aureus) plus standard exit-site care (control group). The primary endpoint was time to first infection related to peritoneal dialysis (exit-site infection, tunnel infection, or peritonitis). The trial is registered with the Australian New Zealand Clinical Trials Registry, number 12607000537459. Of 371 participants, 186 were assigned to the honey group and 185 to the control group. The median peritoneal-dialysis-related infection-free survival times were not significantly different in the honey (16·0 months [IQR not estimable]) and control groups (17·7 months [not estimable]; unadjusted hazard ratio 1·12, 95% CI 0·83–1·51; p=0·47). In the subgroup analyses, honey increased the risks of both the primary endpoint (1·85, 1·05–3·24; p=0·03) and peritonitis (2·25, 1·16–4·36) in participants with diabetes. The incidences of serious adverse events (298 vs 327, respectively; p=0·1) and deaths (14 vs 18, respectively; p=0·9) were not significantly different in the honey and control groups. 11 (6%) participants in the honey group had local skin reactions. The findings of this trial show that honey cannot be recommended routinely for the prevention of peritoneal-dialysis-related infections. Baxter Healthcare, Queensland Government, Comvita, and Gambro.